Media Visual sebagai Sarana Meningkatkan Keterampilan Menulis Teks Persuasif - Anita Candra Dewi (Jurnal Kajian Pendidikan dan Cakrawala Pembelajaran, 2025)
The skill of writing persuasive texts is one of the important competencies in learning Indonesian that requires students to be able to convey ideas with the aim of influencing readers. However, the reality in the field shows that many students have difficulty in writing convincingly, both in terms of content, structure, and language use. This study aims to examine theoretically and empirically how visual media can be used as a means to improve the ability to write persuasive texts at the elementary and secondary education levels. The method used is a literature study by reviewing various journal articles, books, and relevant previous research. The results of the study show that visual media such as images, posters, infographics, and animated videos can stimulate ideas, strengthen arguments, and help students understand the context and structure of persuasive texts more concretely. In addition, visual media also increases student motivation and involvement in the writing process. These findings confirm that the integration of visual media in persuasive writing learning is highly recommended for educators to implement. This study provides implications that teachers need to design creative learning with visual support so that students can express their ideas effectively and persuasively.